Effect of Position Promotion on Passion Employee Working and Culture Services Lamongan District Tourism - Indira Shofia Mulida (Enrichment : Journal of Management, 2020)
The purpose of this study was to determine the effect of job promotion on employee morale the Culture and Tourism Office of Lamongan. The problem of this research that you want to look for is whether or how much influence does a job promotion have on employee morale at the Culture and Tourism Office of Lamongan Regency. In this study, using data analysis, namely, Simple Linear Regression, Correlation Coefficient, t test, and coefficient of determination. The simple linear regression equation shows the result of Y = 16.487 + 0.522 X which shows the influence of job promotion on employee morale. The calculation of the correlation coefficient is 0.464, which means that job promotion has a strong enough effect on employee morale. From the coefficient of determination, the result is 21.5%, indicating the magnitude of the influence of job promotion on employee morale and the remaining 78.5% is influenced by other factors. Then testing the hypothesis using the t distribution table, from the calculation results obtained tcount 3,472> t table 1,680 means that Ho is rejected and H1 is accepted, then the hypothesis proposed by the author can be accepted.